Modifikasi Atmosfir Dalam Pengemasan Untuk Buah Segar - Triyanto Hadisoemarto (Jurnal Kimia dan Kemasan, 1997)
Modified Atmosphere Packaging of Fresh Fruits Many factors must be considered in maintaining the quality of fresh fruits, such as harvesting at optimal maturity, minimizing injury due to handling, reducing microbial infection through proper sanitation, as well as maintaining optimum temperature and humidity. Furthermore, modified atmosphere packaging (MAP) technology, which will be described here, can be used to maintain theproduct quality and to lengthen its shelf life.